Feasibility assessment of palm oil clinker powder as supplementary cementitious material / Mohammad Razaul Karim - Mohammad Razaul , Karim (2017)
Palm oil clinker (POC) is a waste material produced from palm oil shells and mesocarp fibres as fuel to run steam turbines in palm oil mills. The current practice is to dump the waste in the open lands or landfills, which leads to environmental pollution. The current research addresses the question of feasibility of palm oil clinker powder (POCP) as a supplementary cementitious material in cement-based applications. The characterization, chemical interaction, i.e. organic carbon effects and pozzolanic activity of POCP and its influences on fresh and hardened properties of cement were determined for confirmation of the technical suitability as supplementary cementitious material. The greenhouse gas (GHG) reduction and natural resource conservation, radiological hazards and heavy metal leaching toxicity were evaluated for confirming the environmental feasibility of POCP. The characterization and chemical interaction of POCP in cement-based applications were carried out using particle size analyzer, scanning electron microscopy (SEM), ICP-MS, X-ray fluorescence (XRF), field emission scanning electron microscopy and energy-dispersive X-ray (FESEM-EDX), thermogravimetric analysis (TGA), total organic carbon (TOC) analyzer, X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The influence of organic carbon free POCP in strength development was observed at 30% replacement of OPC. The pozzolanic activity was determined by using aforementioned apparatus and through the strength activity measurement. The effect of POCP on the fresh and hardened properties of cement has been determined according to ASTM standard methods. The level of radionuclides and radiological hazard indices were measured using a gamma ray spectrophotometer. The leachibility of heavy metals was carried out according to EPA standard method. The characterization results of POCP confirmed that POCP is composed of a mixture of inorganic oxides with a portion of organic carbon. The XRD pattern and the crystallinity index of POCP confirmed that quartz was partially disordered in the matrix of POCP. Moreover, the right condition for removal of organic carbon from POCP was found to be at 580°C for 3 hours, where the compressive strength of mortar was significantly increased. The microstructure properties investigation and strength activity index confirmed that POCP is a pozzolanic material. The water for normal consistency, setting time and soundness was found within ATSM standard limit up to 60% replacement level. The compressive strength was found to decrease. The incorporation of POCP in cement reduces the cost and the emission of carbon dioxide, and saves the natural resources. The radiological hazard indices of POCP were below the standard limit. However, the value of radium equivalent activity of POCP was found significantly lower than fly ash and was comparable with palm oil fuel ash. Heavy metals were present, but did not leach out from the matrix of POCP more than standard limit. It is safer in terms of radiological and heavy metal leaching risk when used as an ingredient of building material. The POCP is feasible to be used as a supplementary cementitious material in cement-based applications which ultimately leads to lower carbon footprint concrete, cleaner environment and convert waste into a resource.